Interconnectedness and idiosyncratic risks in sub-Saharan forex markets: Implications for investment, portfolio management, and policy formulation - Mariya Gubareva; Vincent Adela; Vo Xuan Vinh (Borsa İstanbul Review, 2025)
This study examines the interconnectedness and idiosyncratic risks in sub-Saharan forex markets from 1999 to 2023. Using the TVP-VAR extended joint connectedness technique, we measure both the static and dynamic extended joint connectivity. Our analysis reveals that sub-Saharan forex markets are significantly influenced by self-induced shocks, with the South African and Namibian Dollars being notable exceptions. It is also observed that the joint total connectedness index for volatility spillovers consistently exceeds that for return spillovers. Additionally, we investigate the drivers of extended joint connectedness and identified mixed effects. Our analysis suggests that GPR, USEPU, MCI, VIX, and OVX asymmetrically influence return and volatility connectedness among sub-Saharan African forex markets. These findings have important implications for policy management and coordination across emerging sub-Saharan African markets.
Keywords: 330; Extended joint connectedness; Forex rates determinants; Return and volatility spillovers; Self-induced shocks; Sub-Saharan forex markets; TVP-VAR